1995
DOI: 10.1002/app.1995.070560507
|View full text |Cite
|
Sign up to set email alerts
|

A study on rheologic behavior of polyphenylene sulfide

Abstract: Rheologic behavior of the common Ryton-type poly(pheny1ene sulfide) (PPS) and Fortron PPS has been studied using a capillary rheometer. The effects of shearing rate, shearing stress, and temperature on the apparent viscosities of PPS are discussed. The non-Newtonian index and the activation energy of the viscous flow were obtained. The results show that the apparent viscosity of the Ryton PPS decreased obviously with increase of shearing rate or shearing stress, and with increase of the temperature, the appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…Therefore, a reduction in the viscosity of the generated PPS molten layer is expected. This result is in agreement with the findings of Hou et al [30]. The authors found that the apparent viscosity of the PPS is dependent both on the shear rate and temperature.…”
Section: Influence Of the Process Parameters On The Pdz Areasupporting
confidence: 94%
“…Therefore, a reduction in the viscosity of the generated PPS molten layer is expected. This result is in agreement with the findings of Hou et al [30]. The authors found that the apparent viscosity of the PPS is dependent both on the shear rate and temperature.…”
Section: Influence Of the Process Parameters On The Pdz Areasupporting
confidence: 94%
“…The thermal degradation mechanism of the Fortron 205 PPS sample is R 3 and the Ryton P‐4 PPS sample is R 2 16. The Fortron PPS sample is believed to possess less chain‐branching than the Ryton PPS sample 27. It seems that because of the branch chain, the thermal degradation mechanism of PPS changed from R 3 to R 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In ref. the research studied the rheological behavior of polyphenylene sulfide (Ryton‐type PPS and Fortron PPS). The results showed that the apparent viscosity of the Ryton PPS decreased obviously with the increase in the shearing rate or shearing stress.…”
Section: Pps—high‐performance Polymer/properties Of Ppsmentioning
confidence: 99%